Exposure to 1,3-butadiene and its possible effects on temple workers and traffic policemen - Manaswee Arayasiri; Mathuros Ruchirawat; Preeda Pakpian; Autrup, Herman; Panida Navasumrit; Chulabhorn Research Institute; Mahidol University; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
Study objectives were, first, to determine the poss ible health risk of temple workers and traffic policemen from 1,3-butadiene exposure b y using biomarkers of exposure and early biological effects, and evaluate confounding factors that may affect on these biomarkers, and second, to study the emission of 1, 3 butadiene from burning incense. 1,3- Butadiene concentrations in the temple and on the r oadsides were significantly larger than in the offices (P < 0.001). Temple workers and traf fic policemen were significantly more exposed to 1,3-butadiene than controls ( p < 0.001). The urinary 1,3-butadiene metabolite, monohydroxy-butenyl mercapturic acid levels in expo sed group were larger than those in controls. 8-Hydroxy -2{u2019}-deoxyguanosine in leukocyte s (8-OHdG), DNA strand breaks, and DNA repair capacity measured by increases in gamma ray induced chromosome aberration, used as biomarkers of early biological effects, have been measured and were significantly larger in exposed workers than contro l subjects. So, temple workers and traffic policemen who are exposed to 1,3-butadiene from burning incense and automobile emissions in their workplaces, are more vulnerable to develop diseases such as cancer than controls.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Engineering in Environmental Engineering and Management Inter-University Program on Environmental Toxicolog y, Technology and Management
Thesis (Ph.D.) - Asian Institute of Technology - Chulabhorn Research Institute - Mahidol University, 2010
Keywords: Traffic police -- Health risk assessment; Butadiene